Role of dentist in genetic counseling: A critical appraisal of the current practices and future requirements in Indian scenario - Ruchika Gupta; B R Chandra Shekar; Pankaj Goel; Sudheer Hongal; Rahul Ganavadiya (Wolters Kluwer Medknow Publications, 2019)
Genetic disorders are showing an upward trend. The social and economic impact of genetic disorders on individual, family and society is enormous. There is an urgent need to explore alternate strategies to mitigate the burden of genetic disorders. This is especially true with regard to developing countries such as India where there is a shortage of health personnel adequately trained in genetic counseling at present. Dental professionals have a unique opportunity to observe the development of preadolescent and adolescent patients during periods when important growth and development changes occur. The objective of this study was to review the existing literature on the role of dentist in genetic counseling with a critical appraisal on the current practices among dentists on genetic services in India, the need, scope, and future requirements. The literature on genetic services and genetic counseling was identified by searching the biomedical databases for primary research material by one investigator over a period of 8 weeks. The articles related to dentist's role in genetic counseling were assessed and discussed in the present review. A total of 239 resource materials were retrieved in the initial search. The literature from these sources was thoroughly scrutinized by the authors, and the literature (review articles, descriptive studies, or any form of study) focusing on role of dentist in genetic counseling was finally considered for critical appraisal in the present review. The role of genetics in health and oral health care has not received due attention of the dental practitioners who otherwise are in a crucial position in identifying the patients with genetic disorders and offer requisite counseling and referral to designated genetic centers. The short training courses for practicing dentists, faculty members, and a small change in dental curriculum to make provision for teaching genetics to undergraduate students may go a long way in filling the void created by these obstacles.